Contribution of School Climate to Student Engagement in Senior High School X Sijunjung - Fanya Puspita Sari; Zulmi Yusra (Causalita, 2024)
Student engagement refers to active, purposeful actions, resilience in facing challenges, and student performance in their interactions with academic activities both in school and outside of school. Student engagement is the involvement of students to participate in academic activities both in school and outside of school which is shown by behavior, emotions, and cognition during their learning. One of the factors that influence student engagement is school climate. The purpose of this study was to determine the contribution of school climate to student engagement. This study is quantitative. Sampling using stratified random sampling with a sample size of 90 people. Data collection uses two scales, namely the school climate scale and student engagement. Research data were analyzed using simple regression analysis. The findings of the study indicate that school climate contributes 5.5% to student engagement. From the regression equation, it is known to have the formula Y = a + Bx, then Y = 48.385 + 0.561X is obtained. Furthermore, the regression coefficient value is 0.561 which means that school climate has a positive contribution to student engagement in students and it can be interpreted that each addition of school climate will increase student engagement by 0.561.